Sing me forgotten - Olson, Jessica S. (Inkyard Press, 2021)
"Cast into a well at birth for being one of the magical few who can manipulate memories when people sing, she was saved by Cyril, the opera house's owner. Since that day, he has given her sanctuary from the murderous world outside. All he asks in return is that she use her power to keep ticket sales high--and that she stay out of sight. For if anyone discovers she survived, Isda and Cyril would pay with their lives. But Isda breaks Cyril's cardinal rule when she meets Emeric Rodin, a charming boy who throws her quiet, solitary life out of balance. His voice is unlike any she's ever heard, but the real shock comes when she finds in his memories hints of a way to finally break free of her gilded prison."--